Human population genetics - Relethford, John H. (Hoboken, New Jersey : Wiley-Blackwell, 2012)
Introductory guide to human population genetics and microevolutionary theory. Providing an introduction to mathematical population genetics, Human Population Genetics gives basic background on the mechanisms of human microevolution. This text combines mathematics, biology, and anthropology and is best suited for advanced undergraduate and graduate study. Thorough and accessible, Human Population Genetics presents concepts and methods of population genetics specific to human population study, utilizing uncomplicated mathematics like high school algebra and basic concepts of probability to explain.
Chapter 1: Genetic, Mathematical, and Anthropological Background -- Chapter 2: Hardy-Weinberg Equilibrium -- Chapter 3: Inbreeding -- Chapter 4: Mutation -- Chapter 5: Genetic Drift -- Chapter 6: Models of Natural Selection -- Chapter 7: Natural Selection In Human Populations -- Chapter 8: Gene flow -- Chapter 9: Human population structure and history.
Includes bibliographical references and index.
Keywords: HUMAN POPULATION GENETICS